From grassroots to global: A blueprint for building a reproducibility network. - UK,Reproducibility Network Steering Committee (PLoS Biol, 2021)
Researchers, institutions, funders, and publishers are considering how to improve research culture and quality, but no single part of the research ecosystem can effect change on its own. The UK Reproducibility Network (UKRN) was established to facilitate the necessary coordination. Its experience can inform the establishment of like-minded networks around the world to drive positive change.